Transient elastography in patients with cystic fibrosis. - Menten R; Leonard A; Clapuyt P; Vincke P; Nicolae AC; Lebecque P; Menten, Renaud; Leonard, Anissa; Clapuyt, Philippe; Vincke, Pierre; Nicolae, Alexandra-Cristina; Lebecque, Patrick (Pediatric Radiology, 2010)
Background: Hepatic involvement is frequent in patients with cystic fibrosis (CF), with focal biliary cirrhosis being the pathognomonic hepatic manifestation. In around one-quarter of CF patients, it results in CF-associated liver disease (CFLD). This occurs as a relatively early complication with the majority of patients presenting in childhood or their early teens. However, a normal US does not preclude significant liver fibrosis and liver biopsy is an invasive procedure that is hampered by potential sampling errors. Transient elastography (TE) (Fibroscan) is a non-invasive, user-friendly and quick technique that provides an objective and reproducible measure of liver stiffness. This is accomplished with a device using an US probe mounted in the axis of a vibrator. Vibrations are transmitted by the transducer, inducing an electronic shear wave that propagates through the underlying tissue.Objectives: We aimed to prospectively compare TE and transabdominal US scanning in children and adults attending a CF clinic.Materials and Methods: A total of 134 consecutive patients with documented CF were prospectively studied. In each case, transient elastography measurement was performed immediately after the routine annual US evaluation of the liver. Sonographic appearance of the liver was classified from 1 to 5. Ten validated TE measurements were performed in each patient with the result expressed in kilopascals (kPa). The median value was considered representative of the elastic modulus of the liver.Results: Measurements were performed in 59 CF adults, 75 CF children and 31 control children. There was no relationship between age and liver stiffness in either the control group or CF patients. Elasticity values of controls, CF pancreatic sufficient (PS) patients and pancreatic insufficient (PI) CF patients with a US score <3 were comparable and significantly lower than in CF patients with a US score > or = 3 (all PI) (P < 0.002). Median elasticity in CF patients was significantly higher in males (4.7 kPa) than in females (3.9 kPa) (P = 0.0013).Conclusion: Considering the limitations of US and the low risk-benefit rate of liver biopsy in most CF patients, this preliminary study suggests that TE is an attractive non-invasive way to assess and follow-up liver disease in these patients.